Green revolution for the Sahel - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
An agricultural revolution based on cowpeas awaits farmers in the semi-arid belt that stretches across West Africa where there is an opportunity to develop the area into a more productive livestock fattening region to meet help the demands of the...